2019
DOI: 10.1002/anie.201909698
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Doping and Intercalation: Realizing Deep Phase Modulation on MoS2 Arrays for High‐Efficiency Hydrogen Evolution Reaction

Abstract: As ynergistic Nd oping plus PO 4 3À intercalation strategy is used to induce high conversion (ca. 41 %) of 2H-MoS 2 into 1T-MoS 2 ,which is muchhigher than single Ndoping (ca. 28 %) or single PO 4 3À intercalation (ca. 10 %). Ascattering mechanism is proposed to illustrate the synergistic phase transformation from the 2H to the 1T phase,w hich was confirmed by synchrotron radiation and spherical aberration TEM. To further enhance reaction kinetics,t he designed (N,PO 4 3À )-MoS 2 nanosheets are combined with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
139
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 228 publications
(144 citation statements)
references
References 55 publications
5
139
0
Order By: Relevance
“…XANES spectra (Ti L-edge) were measured at beamline station BL12B in National Synchrotron Radiation Laboratory (NSRL, operated at 800 MeV with a maximum current of 300 mA) of China. The samples were placed on double-sided carbon tape for X-ray spectroscopy and all spectra were obtained with the TEY mode 37 . The "a.u."…”
Section: Methodsmentioning
confidence: 99%
“…XANES spectra (Ti L-edge) were measured at beamline station BL12B in National Synchrotron Radiation Laboratory (NSRL, operated at 800 MeV with a maximum current of 300 mA) of China. The samples were placed on double-sided carbon tape for X-ray spectroscopy and all spectra were obtained with the TEY mode 37 . The "a.u."…”
Section: Methodsmentioning
confidence: 99%
“…But the adopted substrate was rigid TiC/C‐Ti 6 Al 4 V, which could not be used as flexible configuration. Meanwhile, it is reported that PO 4 3− ion intercalation can induce defects on metal sulfides/oxides (e.g., MoS 2 , Co 3 O 4 ) to achieve enhanced intrinsic reaction kinetics. Inspired by these results, it would be very interesting to explore PO 4 3− ion intercalated MnO 2 /VMG arrays and their flexible zinc ion storage performance, but not reported as yet.…”
Section: Introductionmentioning
confidence: 99%
“…Two peaks at around 229.6 and 232.9 eV can be ascribed to Mo 3d 5/2 and Mo 3d 3/2 , respectively, revealing that molybdenum is in its Mo(IV) state. 26,27 Two peaks which are located at 162.6 and 163.7 eV can be ascribed to S 2p 3/2 and S 2p 1/2 , respectively. 28 These results indicate the presence of Mo 4+ and S 2À species within the CC@MoS 2 precursor.…”
Section: Resultsmentioning
confidence: 99%